Pengaruh Komunikasi Internal, Konflik Kerja dan Disiplin Kerja terhadap Semangat Kerja Karyawan pada Desa Pramana Swan Villa Keramas di Gianyar - Putri Utami, Ni Wayan; Wulandari, Ni Luh Adisti Abiyoga; Oktarini, Luh Nik (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
High employee morale helps the company quickly achieve company goals, so good internal communication between colleagues is needed, minimal work conflicts in the workplace, and maintaining employee discipline so that employees remain enthusiastic at work. The purpose of this study was to test the influence of internal communication, labor disputes and work discipline on the morale of employees in Pramana Swan Villa Keramas Gianyar Village.  The total population and sample in this study were 42 respondents determined by the saturated sampling method. Data collection method with observation, interviews, literature studies and questionnaires. Data analysis techniques use validity and reliability research instrument tests, classical assumption tests, multiple linear regression analysis, termination coefficient analysis, F test and T test. Based on the results of the analysis, the results of this study, namely internal communication, partially have a positive and significant effect on morale. Work conflict partially negatively and significantly affects morale and work discipline partially has a positive and significant effect on morale.